A domain-based query routing mechanism for peer-to-peer networks - Hassan, Ghada; Ibrahim, Hamidah; Sulaiman, Md. Nasir; Yakob, Rasali (Elsevier, 2011)

(untitled)
In recent years, peer-to-peer (P2P) technology is widely used and concerned by both academic and industry. An important challenge associated with this technology is the routing of content-based queries (i.e. locating the peers that can provide the answer) in P2P networks that contain large number of heterogeneous nodes. This challenge is mainly due to the decentralized distribution of the content among the large number of peers. To cope with this challenge, the proposed mechanisms have their own weaknesses to be a successful solution, since they suffer from high values for both number of messages per query and the response time. In this paper, we propose a new query routing mechanism to improve query routing performance in such P2P networks. The fundamental idea in the proposed mechanism is to limit the search space to a given query around the related peers. Therefore, the mechanism consists of a domain based architecture for grouping peers in the network into domains based on their contents. In each domain, interconnected groups of peers are constructed based on attributes analysis process. To perform the query routing, the mechanism provides the required methods for specifying the interaction between the peers in the same or different groups. To validate our mechanism, an experimental study is conducted to compare the performance of the proposed mechanism with a baseline mechanism. The results show that the proposed mechanism achieves better performance with respect to the reduction of the average number of messages per query, the average search path length and the response time.